Application of Chinese Miao Tribe Typical Embroidery and Beadings in Women's Ready-to-Wear Clothing - Lunardi, Ardisa Devana; Aryani, Dewi Isma (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2024)
In modern times, more and more women's roles and emancipation have emerged in almost all fields. The role of these women is even seen in several cultures and beliefs in the world, one of which is the Miao New Year Festival in China. The participation of Miao tribal women in the annual festival became a source of inspiration for designing a ready-to-wear collection entitled MINZU. The MINZU collection packs a symbol of Miao belief in a modern form so that it can be accepted and used by urban residents in big cities. The MINZU collection features a jacket silhouette typical of China combined with traditional Miao clothing to display the overall impression of ethnicity. The modern impression is obtained by applying several material manipulations, namely embroidery and beads. The objectives of this design are to: 1) Create a ready-to-wear women's clothing collection with the inspiration of the Miao New Year festival, 2) Apply material manipulation techniques in the form of embroidery and beads typical of the Miao tribe to the urban women's clothing collection. The method used is the PBL (Project Based Learning) method, which is the learning method that uses real projects through information search and data synthesis, material exploration, feasibility assessment, and design interpretation to produce final results.